Tardigrades from Guizhou Province (China) with description of a new species of genus Doryphoribius (Tardigrada: Hypsibiidae) - Wang, Hanping; Wang, Lizhi; Li, Xiaochen (Zootaxa, 2007)
Seventeen species of tardigrades were found in this study. All species are new records for Guizhou Province, including two new records for China (Echiniscus perviridis and Doryphoribius zappalai) and one (Doryphoribius huangguoshuensis sp. nov.) new for science. The new species differs from the most similar species of the genus Doryphoribius mainly by different configuration of gibbosities on dorsal side of the body (configuration 4, 4, 4, 4, 4, 4, 4, 2, 2 in the new species; 2, 2, 2, 2, 2, 2, 2 in D. dupliglobulatus; 4, 4, 4, 4, 4, 4, 4, 2, 2, 3 in D. gibber; 6, 4, 6, 4, 6,4, 4, 2 in D. zyxiglobus).